Navigating the choice of oral anticoagulation therapy for atrial fibrillation in the NOAC era. (December 2017) - Hammersley, Daniel; Signy, Mark
Atrial fibrillation (AF) is a major cause of ischaemic stroke. The majority of these strokes can be prevented by treatment with oral anticoagulation therapy. The advent of non-vitamin K antagonist oral anticoagulants (NOACs) has resulted in a choice of therapeutic agents available to physicians for anticoagulation for stroke prevention in patients with AF beyond the long-established vitamin K antagonists (VKAs). Pivotal trials have demonstrated non-inferiority of NOACs compared with VKAs, and in some cases superiority, for the prevention of stroke and systemic embolism in non-valvular AF. Yet there are no direct head-to-head comparator trials for the efficacy of NOACs. Therefore, the question of which oral anticoagulant for each individual patient can present a challenge to physicians. In this review article, we assess which patients with AF require anticoagulation, review the available therapeutic options, assessing the evidence base for each and offering guidance as to patient-specific factors that can influence this choice.